Network Neutrality Regulation in Brazil: An Economic Sociology Approach and the Challenges After the FCC's Decision - Emerson Leonardo Schmidt Iaskio; Morten Falch; Walter Tadahiro Shima (International Telecommunications Society (ITS), 2018)
Why different groups have different opinions on network neutrality? Can a group impose their opinion to others and have their claims respected by the regulatory authorities? This paper aims to present some insights about the network neutrality regulation in Brazil and discuss the challenges after the FCC's decision in the United States regarding network neutrality. It is hypothesized that there are conflicting groups and that such groups will seek, in the open discussions, to impose their calculation devices. The process of implementation and regulation of the Brazilian Civil Landmark of the Internet is a conflict arena, in which the actors could present their world views and their calculation devices.
Keywords: 330; Network neutrality; Regulation; FCC